2006
DOI: 10.1111/j.1442-2042.2006.01366.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute necrotizing pancreatitis as a rare complication of extracorporeal shock wave lithotripsy

Abstract: Extracorporeal shock wave lithotripsy (ESWL) is considered the standard treatment for most renal and upper ureteral stones. Some centers use ESWL to treat bile duct stones and pancreatic calculi. Although ESWL is generally considered safe and effective, major complications, including acute pancreatitis, perirenal hematoma, urosepsis, venous thrombosis, biliary obstruction, bowel perforation, lung injury, rupture of an aortic aneurysm and intracranial hemorrhage, have been reported to occur in less than 1% of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 8 publications
(13 reference statements)
0
20
0
1
Order By: Relevance
“…Others have also shown similar temporal profiles for serum lipase and amylase after renal SWL. 5,7,8 The rise in serum markers of pancreatic exocrine function observed in the present study likely reflects pancreatic trauma as collateral damage of renal SWL, but they remained within or close to normal limits. Regardless, we were able to confirm injury to the pancreatic tail histologically—sites of hemorrhage, chronic inflammation, loss of normal cell integrity, fibrotic regions and loss of insulin-immunoreactive beta cells.…”
Section: Discussionmentioning
confidence: 58%
“…Others have also shown similar temporal profiles for serum lipase and amylase after renal SWL. 5,7,8 The rise in serum markers of pancreatic exocrine function observed in the present study likely reflects pancreatic trauma as collateral damage of renal SWL, but they remained within or close to normal limits. Regardless, we were able to confirm injury to the pancreatic tail histologically—sites of hemorrhage, chronic inflammation, loss of normal cell integrity, fibrotic regions and loss of insulin-immunoreactive beta cells.…”
Section: Discussionmentioning
confidence: 58%
“…Several reports in the literature are present regarding the possible harmful effect of extracorporeal SWL on the kidneys and adjacent organs: the lungs, liver, pancreas, and intestine. [1][2][3][4][5] Perirenal hematoma with or without hematuria is the most common acute complication. Transient increase in intrarenal vascular resistance, diastolic blood pressure, and markers of tubular damage was reported after SWL.…”
mentioning
confidence: 99%
“…12,13 Diabetes mellitus was reported as a late complication after SWL due to acute necrotizing pancreatitis. 2,11 The majority of the studies about the side effects of SWL investigated the parenchymal damage and renal function, however, only few studies investigated the possible effect of SWL on the peristaltic movement of the ureter. 14,15 Recently, we have published a study where the effect of electrohydraulic lithotripter on the urothelial and muscle layer of the ureter and kidney was investigated.…”
mentioning
confidence: 99%
“…10,27,28 In our series, we showed that the implementation of technical improvements (ie, location system and focusing) achieved with the latest generation of lithotripters further reduced the incidence of adverse events, particularly the incidence of serious adverse events.…”
Section: Discussionmentioning
confidence: 87%